Designing and testing novel artificial shelter traps to mass-trap overwintering brown marmorated stink bugs: a proof-of-concept study in Northwestern China - Jin-Ping Zhang; Gonzalo Avila; Gang Ma; Qian-Qian Mi; Adriana Najar-Rodriguez; Ju-Hong Chen; Chun-Sen Ma; Feng Zhang (CABI Agriculture and Bioscience)
Abstract Background Halyomorpha halys Stål (Hemiptera: Pentatomidae), brown marmorated stink bug (BMSB), is a highly polyphagous invasive pest worldwide. It is also known to be a nuisance pest as it enters artificial structures, including human habitats, to overwinter and releases very unpleasant odours when disturbed. Overwintering populations can be trapped and killed collectively by targeting the aggregation behaviour of BMSB adults. However, efficient traps for catching overwinter population have not been yet developed and validated. A novel and effective trapping method would be to design shelter traps in the field that entice and mass-trap overwintering BMSB as they initiate to display their typical aggregation behavior and seek shelter in the traps. Methods In this study conducted in Northwestern China, we designed different BMSB overwintering shelter traps made of different materials (i.e., wood or corflute) and lock types (with/without lock, pyrometric or strip door lock) and tested their efficacy at two different sites and three different locations within sites. We also tested the efficacy of the traps with or without the presence of the BMSB aggregation pheromone. Results Although trapped BMSB numbers were generally low across all traps tested, the black corflute trap was found to attract the highest average number of BMSB males and females, followed by the wooden-made trap, the bee-hive box and finally the wooden-made locked trap, which attracted the lowest numbers of BMSB. The trapping efficacy was found to not be affected by experimental sites or locations nor by the presence of the BMSB aggregation pheromone lure. Conclusions Our results showed that traps made of black corflute with slit doors were generally preferred by overwintering BMSB. This preliminary proof-of-concept study provides valuable information for further improvement of novel overwintering traps that could be used to mass trap BMSB overwintering populations.